2012
DOI: 10.3390/ijms13056156
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Rapid Molecular Techniques for Identification of Amylose Levels in Rice Varieties

Abstract: The polymorphisms of Waxy (Wx) microsatellite and G-T single-nucleotide polymorphism (SNP) in the Wx gene region were analyzed using simplified techniques in fifteen rice varieties. A rapid and reliable electrophoresis method, MetaPhor agarose gel electrophoresis (MAGE), was effectively employed as an alternative to polyacrylamide gel electrophoresis (PAGE) for separating Wx microsatellite alleles. The amplified products containing the Wx microsatellite ranged from 100 to 130 bp in length. Five Wx microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
(42 reference statements)
1
13
0
2
Order By: Relevance
“…Conversely, Cheng et al (2012) identified intron1 is insufficient to explain the genetic variations of AC in rice. Therefore, the study based on the AC and molecular analysis would be helpful for the selection of appropriate nutritional quality rice for diabetic.…”
Section: Nutritional and Nutraceutical Properties Of Ricementioning
confidence: 99%
“…Conversely, Cheng et al (2012) identified intron1 is insufficient to explain the genetic variations of AC in rice. Therefore, the study based on the AC and molecular analysis would be helpful for the selection of appropriate nutritional quality rice for diabetic.…”
Section: Nutritional and Nutraceutical Properties Of Ricementioning
confidence: 99%
“…and 5 min at 72 °C for the final extension. PCR products from fgr-SNP for foreground selection 140 D r a f t were separated on standard 1% agarose gel at 100 V for 1 h, while products from the SSR 141 markers for background selection were separated on high resolution 3% MetaPhor agarose gel at 142 80 V for 3.5 h. The 3% MetaPhor agarose gel was prepared following the protocol described by 143 Cheng et al (2012). The resolved PCR bands were detected by staining the agarose or MetaPhor 144 agarose gels for 30 s with ethidium bromide (EtBr), followed by destaining for 30 min in 145 distilled water and visualisation with a UV gel imager (Alpha Innotech, USA).…”
Section: Plant Materials 100mentioning
confidence: 99%
“…Amylose content is often contributed, to the differences in cooking and eating qualities of rice about 65 % (Juliano, 1971). Cheng et al (2012) reveal, higher amylose tends to absorb more water during the cooking process and resulting higher volume expansion of rice. After cooking, it receives dry and fluffy texture and grains can be separated easily.…”
Section: Introductionmentioning
confidence: 99%